The Shallow-water Crinoid Fauna of Lakshadweep Atolls, North-western Indian Ocean - Mohammednowshad, B.; Idreesbabu, K.k.; Parameswaran, Usha V.; Messing, Charles G.; Sureshkumar, S. (Zootaxa, 2020)
A biodiversity survey carried out from 2016 to 2018 by the Department of Science and Technology in the Lakshadweep Atolls, India, recorded six species of shallow-water feather stars new to the archipelago (Comanthus wahlbergii, Comaster schlegelii, Himerometra robustipinna, Dichrometra palmata, Stephanometra indica, and Phanogenia typica). Himerometra sol A.H. Clark, 1912, previously known only from the Maldive Islands, is synonymized under Himerometra robustipinna (Carpenter, 1881). This study brings the total number of shallow-water crinoids recorded from Lakshadweep to ten species. Of the four species collected previously from the archipelago, only Comatella nigra was found in this survey. Of those not collected, Comatella stelligera and Oligometra serripinna are widespread in the Indo-western Pacific region, whereas Heterometra compta is known only from Lakshadweep, and its validity remains uncertain. The known shallow-water crinoid fauna of the archipelago is substantially less diverse than that of the adjacent and environmentally similar Maldive Islands, emphasizing the need for additional research in this island group, in particular, to determine whether the differences are actual or not, and whether they are based on natural conditions versus anthropogenic impacts.